2008
DOI: 10.1073/pnas.0805980105
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a functional and durable vascular niche by the adenoviral E4ORF1 gene

Abstract: angiogenesis ͉ endothelium ͉ adenovirus ͉ tumor ͉ stem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
157
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 12 publications
2
157
0
Order By: Relevance
“…These investigators also suggested that leukemic cell-induced upregulation of VEGFR2 signaling in E4ORF1 ECs led to the elaboration of angiocrine factors that promoted leukemic cell growth. 19,98 Taken together, these studies suggest that leukemic cells elaborate growth factors, which augment EC proliferation, and ECs symbiotically mediate the proliferation and survival of leukemic cells. 19,92,[96][97][98] In addition to the contribution of the BM vascular niche and other niche cells to leukemic cell growth, BM-derived ECs and stromal cells also regulate the establishment of metastatic niches for solid tumor cells.…”
Section: Do Ecs Secrete Soluble Growth Factors That Mediate Hsc Self-mentioning
confidence: 99%
See 2 more Smart Citations
“…These investigators also suggested that leukemic cell-induced upregulation of VEGFR2 signaling in E4ORF1 ECs led to the elaboration of angiocrine factors that promoted leukemic cell growth. 19,98 Taken together, these studies suggest that leukemic cells elaborate growth factors, which augment EC proliferation, and ECs symbiotically mediate the proliferation and survival of leukemic cells. 19,92,[96][97][98] In addition to the contribution of the BM vascular niche and other niche cells to leukemic cell growth, BM-derived ECs and stromal cells also regulate the establishment of metastatic niches for solid tumor cells.…”
Section: Do Ecs Secrete Soluble Growth Factors That Mediate Hsc Self-mentioning
confidence: 99%
“…19,98 Taken together, these studies suggest that leukemic cells elaborate growth factors, which augment EC proliferation, and ECs symbiotically mediate the proliferation and survival of leukemic cells. 19,92,[96][97][98] In addition to the contribution of the BM vascular niche and other niche cells to leukemic cell growth, BM-derived ECs and stromal cells also regulate the establishment of metastatic niches for solid tumor cells. 59,99,100 Lyden et al 101 showed that blockade of recruitment of BM ECs and BM HPCs to metastatic sites impairs tumor angiogenesis and cancer growth in vivo.…”
Section: Do Ecs Secrete Soluble Growth Factors That Mediate Hsc Self-mentioning
confidence: 99%
See 1 more Smart Citation
“…E4 þ ECs were obtained as previously described (22). Briefly, isolated HUVECs were transduced with the early 4 region (E4) of the adenoviral vectors (AdE4 þ ) to generate durable PEC feeders.…”
Section: Cell Culturementioning
confidence: 99%
“…We demonstrated that the cross-talk between ovarian cancer cells (OCC) and established human umbilical vein endothelial cell line (HUVEC) resulted in an activation of Akt pathway among others. To model tumor endothelium, we used the Akt-activated endothelial cells (E4 þ ECs) to study the involvement of the endothelial component in the resistance to antiangiogenic therapy (22). We demonstrated that in the setting of tumor-endothelial cross-talk, endothelial cell activation of PI3K/Akt pathway induces an autocrine loop through the proangiogenic factor FGF2, bypassing the VEGFR pathway.…”
Section: Introductionmentioning
confidence: 99%